'Black girl magic, y'all can't stand it, y'all can't ban it': Black girl curated curricula unsettling the conventional reason of school. Issue 2 (4th March 2021) - López López, Ligia (Licho); Nikey
ABSTRACT: Being in curriculum is the cry of the damné to call for attention to one's existence against the antiblack and antibrown 'weather' in schools. This paper draws from the cry of young people, particularly Black girls to say 'I am here' in curriculum. Drawing from two years of primary/elementary classroom research in the United States, this paper presents the curatorial work Black girls offered to the school curriculum. Through the political intervention of generating curriculum from the popular visual cultures young people engage in, Black girls' classroom participation and their careful selection of visual texts offered a glimpse towards inventing education otherwise. With statements by Black girls that stage a curricular revolt, this paper points to the infinite possibilities for opening up new frontiers of being in times of intensified attacks on Black and Brown lives as alters of the 'absolute model of the Human'.